ICT, Collaboration, and Science-Based Innovation: Evidence from BITNET - Kathrin Wernsdorf; Markus Nagler; Martin Watzinger (Center for Economic Studies and Ifo Institute (CESifo), 2020)
Does access to information and communication technologies (ICT) increase innovation? We examine this question by exploiting the staggered adoption of BITNET across U.S. universities in the 1980s. BITNET, an early version of the Internet, enabled e-mail-based knowledge exchange and collaboration among academics. After the adoption of BITNET, university-connected inventors increase patenting substantially. The effects are driven by collaborative patents by new inventor teams. The patents induced by ICT are exclusively science-related and stem from fields where knowledge can be codified easily. In contrast, we neither find an effect on patents not building on science nor on inventors unconnected to universities.
Keywords: H54; L23; L86; O30; O32; O33; 330; ICT; communication; knowledge diffusion; science-based innovation; university-patenting